NHT Learning Model Based on Digital Gamification Platforms (Genially) to Enhance Elementary School Students’ Numeracy Skills - Nur Inda Sari Rahmawati; Moh. Rudini; Muh. Khaerul Ummah BK (Program Studi PGSD Universitas Madako Tolitoli, 2026)
This study is aimed at enhancing the numeracy skills of fourth-grade students in Class IV B at SDN 2 Nalu through the implementation of the cooperative learning model known as NHT, integrated with digital gamification media based on Genially. The subjects of this research were SDN 2 Nalu’s students, and the study was conducted in two cycles. This research employed a Classroom Action Research (CAR) approach carried out over two cycles. The findings indicate a significant improvement in students’ numeracy achievement. Learning mastery, which was initially at 40%, increased to 75% in the first cycle and reached 100% in the second cycle. In addition, both student learning activities and teacher performance showed continuous improvement, ultimately reaching a “very good” category by the end of the study. These findings confirm that the implementation of the NHT cooperative learning model supported by Genially-based digital gamification media is highly effective in improving the numeracy skills of fourth-grade students at SDN 2 Nalu. Furthermore, this study contributes to the advancement of adaptive, contextual, and sustainable technology-based learning innovations and holds potential as a foundation for future research in the field of primary education technology and the strengthening of numeracy literacy in the digital era.